2009
DOI: 10.1117/12.820853
|View full text |Cite
|
Sign up to set email alerts
|

Human factors guidelines for applications of 3D perspectives: a literature review

Abstract: Once considered too processing-intense for general utility, application of the third dimension to convey complex information is facilitated by the recent proliferation of technological advancements in computer processing, 3D displays, and 3D perspective (2.5D) renderings within a 2D medium. The profusion of complex and rapidly-changing dynamic information being conveyed in operational environments has elevated interest in possible military applications of 3D technologies. 3D can be a powerful mechanism for cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The use of VR in education is so new, and its affordances are of such a multitude, that design guidelines solely for education in VR have not yet been published. A meta-analysis commissioned by the US military (Dixon et al, 2009 ) found 400 documents that had the words “2D, 2.5D, and 3D applications for information visualization, display development, and guidelines for applications of dimensionality.” The search stopped in the year 2006. The study reports benefits when 3D technology was used to:…”
Section: Vr and Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of VR in education is so new, and its affordances are of such a multitude, that design guidelines solely for education in VR have not yet been published. A meta-analysis commissioned by the US military (Dixon et al, 2009 ) found 400 documents that had the words “2D, 2.5D, and 3D applications for information visualization, display development, and guidelines for applications of dimensionality.” The search stopped in the year 2006. The study reports benefits when 3D technology was used to:…”
Section: Vr and Educationmentioning
confidence: 99%
“…p. 11. Dixon et al (2009) found few studies that, if they reported on human performance at all, were not tied to performance with specific equipment. Thus, the findings were somewhat narrow and non-generalizable.…”
Section: Vr and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The principles and practices of the combined framework must be presented in a way that practitioners can understand and apply them in their teaching and learning. Although guidelines exist to support the design of VR military applications (eg, Dixon, Fitzhugh & Aleva, ) and the design of the buildings and other objects within the VWs (eg, Saleeb & Dafoulas, ), more work is required in creating guidelines for educational applications and more critically for evaluating their acceptability and effectiveness.…”
Section: Further Researchmentioning
confidence: 99%
“…,Leeds, & Winer, 1988;Haskell & Wickens, 1993;Wickens, 2000;St. John, Cowen, Smallman, & Oonk, 2001; see reviews byNaikar, 1998, andDixon, Fitzhugh, &Aleva, 2009), but nearly all these works utilize flat 2D displays to show 2D images of 3D perspective geometry (sometimes called 2½D). These are not literally true depth displays in the same sense that stereoscopic displays are 3D because they do not require the binocular visual system.…”
mentioning
confidence: 99%